Evaluation of solvent swelling pre-treatment combined with ammonia leaching using waste etchant from printed circuit board manufacturing for copper recovery from waste printed circuit boards - Kondo, Takunda (Department of Chemical Engineering, 2023)
Electronic waste (e-waste) has emerged as a rapidly growing waste stream, growing at a global rate of 2 Mt per annum and is expected to exceed 74 Mt by 2030. E-waste contains a high content of precious and base metals which can be recovered for economic benefit. This has made the recycling of this waste stream of interest, with particular emphasis on the recovery of metals from waste Printed Circuit Boards (PCBs) as they contain a high content of copper as well as a significant quantity of precious metals such as gold, silver, and palladium. The major economic driver for the beneficiation of PCBs is the recovery of these precious metals followed by the recovery of copper which can constitute more than 20% of the value share. In the South African context, 5-7% of e-waste generated is collected and formally recycled. There exists potential to increase the proportion of e-waste recycled through the development of accessible beneficiation techniques that can be implemented by small scale industries. This study builds on previously completed research on alkaline ammonia leaching for the recovery of copper from waste PCBs that have undergone various physical or chemical pretreatment processes for metal liberation. Some PCB manufacturing processes employ a similar alkaline ammonia oxidative leaching system as one of the key process-steps in the manufacturing of PCBs as is evident by the case study of a local PCB manufacturing company. There exists an opportunity to utilize waste etchant from the manufacturing process as lixiviant for the recovery of copper from waste PCBs. This will enhance resource efficiency in line with the United Nations sustainable development goal 12, responsible consumption and production by extracting value from both the copper loaded waste etchant and waste PCBs. The potential to recover copper from both waste PCBs and the waste etchant through a leach circuit that utilizes the excess lixiviant contained in the waste etchant is explored. To do this, the copper distribution of a custom-made 4-layer PCB is established through a breakdown of the readily accessible top and bottom surface copper, referred to as the “surface copper” as well as the tightly laminated inner layer copper inaccessible to the lixiviant. Pre-treatment utilizing chemistry from the PCB manufacturing desmear process is then explored as a viable pretreatment method for liberating the inner layer copper with a key focus on solvent swelling with N-Methyl-2-pyrrolidone (NMP) and NMP based solvent (Solvent B). The characterization of the custom-made PCB determined that 47.2% of the copper was located on the surface of the PCB and 52.8% in the inner layers. The success of the solvent swelling pre-treatment is measured by the extent to which this 52.8% is unlocked for access by the lixiviant. The degree of metal liberation by the chemical pre-treatment method employed was determined by diagnostic column leaching using primarily samples of waste etchant from a local PCB manufacturing factory as well as synthetic etchant modelled after a typical waste etchant stream. Solvent swelling yielded good recoveries above 90%, with NMP solvent swelling at 150C achieving the highest copper recovery of the two solvents at 93.4%. It was found that the PCBs that did not undergo solvent swelling yielded recoveries mostly from the surface copper with a recovery of 50% from boards that had been soaked in sodium hydroxide for removal of the solder mask coating. A combination of both physical and chemical pretreatment by combining 6 pass shredding with solvent swelling yielded a copper recovery of 68.9% using Solvent B. This was comparable to 88.4% obtained from solvent swelling with the same solvent. Solvent swelling alone was found to be an effective method for liberating copper from the inner layers and combining swelling with mechanical shredding was found to yield lower copper recoveries as a result of the preg-robbing phenomenon. Three lixiviant systems were analyzed for performance, namely ammonium sulphate, waste etchant and synthetic etchant. Of the three, ammonium sulphate with initial copper concentration of 100 ppm was significantly outperformed in leaching rate by waste etchant and synthetic etchant which required shorter leaching times to recover the readily accessible surface copper, however waste etchant was found to have limitations of copper saturation leading to precipitation due to its high copper content.